Effect of Nano Zeolite Filler Substitution on Marshall and Volumetric Characteristics of AC-WC Mixtures - Romaynoor Ismy; Ammar Fadhil; Idayani; Hanyta Khairunnisa (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2026)
The performance of Asphalt Concrete–Wearing Course (AC-WC) mixtures is strongly influenced by filler characteristics that control mechanical resistance and volumetric stability. Although nano zeolite has demonstrated potential for improving asphalt mixture performance, previous studies mainly focus on binder modification or advanced performance-based tests, limiting their applicability in routine mix design practice. Consequently, the role of nano zeolite as a filler substitute in conventional hot mix AC-WC mixtures evaluated using fundamental Marshall parameters remains insufficiently explored, and the optimum substitution level for practical pavement applications has not been clearly established. This study aims to evaluate the effect of nano zeolite filler substitution on the Marshall and volumetric characteristics of AC-WC mixtures and to determine the optimum substitution level based on standard mix design criteria. The Optimum Asphalt Content (OAC) was determined at 6.04% and applied as a constant asphalt content. Nano zeolite was used as a partial replacement of cement filler at substitution levels of 0%, 25%, 50%, 75%, and 100%. Evaluated parameters included Marshall stability, flow, Marshall Quotient (MQ), density, VIM, VMA, and VFA. The results indicate that a 50% nano zeolite substitution yields the optimum performance, producing the highest Marshall stability and MQ while satisfying specification limits. These findings provide practical guidance for applying nano zeolite as an alternative filler in AC-WC mixtures using conventional Marshall based mix design.